KONSEP PEMIKIRAN PENDIDIKAN ISLAM MENURUT KH. HASYIM ASY’ARI - Lastri Khasanah (STAI Sufyan Tsauri Majenang, 2020)
KH. Hasyim Asy'ari is a Scholar, founder of the Tebuireng pesantren, and founder of NU (Nahdlatul Ulama), the largest religious organization in Indonesia. He pays attention to education very much. KH. Hasyim Asy'ari suggests education is very important for human for becoming dignified and noble, and creating a cultured and ethical society. The concept of thinking in education includes the virtues of science and scientists, the importance of teaching and learning, ethics that must be considered in teaching and learning namely the ethics of a student towards a teacher, the ethics of a student towards a lesson and the things that must be followed with the teacher, and the ethics of the teacher in teaching. His educational thinking has changed the face of pesantren which seems to be traditionally only focused on religious knowledge, into a form of pesantren that open and accepting a change. The renewal carried out is by introducing the madrasah learning system and incorporating general education in addition to religious education.